Cho \(\displaystyle\int\limits_1^3\dfrac{x+3}{x^2+3x+2}\mathrm{\,d}x=a\ln2+b\ln3+c\ln5\) với \(a\), \(b\), \(c\) là các số nguyên. Giá trị của \(a+b+c\) bằng
\(0\) | |
\(2\) | |
\(3\) | |
\(1\) |
Chọn phương án B.
Đặt $A=\displaystyle\int\limits_1^3\dfrac{x+3}{x^2+3x+2}\mathrm{\,d}x$ ta có $$A=\ln2^a3^b5^c\Leftrightarrow\mathrm{e}^A=2^a3^b5^c.$$
Vì $a,\,b,\,c\in\mathbb{Z}$ nên $2^a3^b5^c\in\mathbb{Q}$.
Vì $\dfrac{12}{5}=4\cdot3\cdot\dfrac{1}{5}=2^2\cdot3^1\cdot5^{-1}$ nên $a=2$, $b=1$ và $c=-1$.
Khi đó $a+b+c=2$.
Chọn phương án B.
\(\begin{aligned}
\displaystyle\int\limits_1^3\dfrac{x+3}{x^2+3x+2}\mathrm{\,d}x&=\displaystyle\int\limits_1^3\dfrac{x+3}{(x+1)(x+2)}\mathrm{\,d}x\\
&=\displaystyle\int\limits_1^3\left(\dfrac{2}{x+1}-\dfrac{1}{x+2}\right)\mathrm{\,d}x\\
&=\left(2\ln|x+1|-\ln|x+2|\right)\bigg|_1^3\\
&=2\ln2+\ln3-\ln5.\end{aligned}\)
Theo đó \(a=2,\,b=1,\,c=-1\).
Suy ra \(a+b+c=2\).
Giả sử \(\dfrac{x+3}{(x+1)(x+2)}=\dfrac{A}{x+1}+\dfrac{B}{x+2}\)
\(\Leftrightarrow\dfrac{x+3}{(x+1)(x+2)}=\dfrac{(A+B)x+2A+B}{(x+1)(x+2)}\)
Đồng nhất hệ số ta được $$\begin{cases}A+B&=1\\ 2A+B&=3\end{cases}\Leftrightarrow\begin{cases}A=2\\ B=-1.\end{cases}$$
Vậy \(\dfrac{x+3}{(x+1)(x+2)}=\dfrac{2}{x+1}-\dfrac{1}{x+2}\).